Impact of Ownership Structure and Firm Size on the Operational Risk Management of Islamic Banks in Pakistan - ADNAN; Dr. MUHAMMAD IBRAHIM KHAN; Dr. MUHAMMAD IBRAHIM KHAN; SYED IMRAN KHAN (Journal of Business & Tourism, 2021)
This study investigates the impact of ownership structure and firm size on the operational risk management (ORM) in the context of Islamic banks in Pakistan. ORM is the excess capital acquired after subtracting actual capital from minimum capital required for handling operational risk. While, the bank size is measured as deposit plus advances or log of total assets. The Basic Indicator Approach (BIA), and Standardize Approach (STA) is used to measure the minimum capital required for managing operational risk. A panel data set of 19 Islamic banks listed on the Pakistan Stock Exchange (PSX) is analyzed over the period from 2012 to 2016.Three important observations are provided by the results; first increase in the size of the Islamic banks tend to lower the surplus capital maintain by banks for managing operational risk. Second, a significant positive relationship is reported between excess capitals required for managing operational risk and public owned Islamic banks. Third, the results are reported as robust as all three regression model provided similar results.